UJI KUALITATIF ASESMEN AUTENTIK BUKU AJAR EVOLUSI MOLEKULER PADA MAHASISWA JURUSAN BIOLOGI FMIPA UNIVERSITAS NEGERI MALANG - Rahmawati D; Mohamad Amin; Umie Lestari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
Evolutionary course materials in the Biology Department, State University of Padang inadequate to guide students to think critically, giving rise to various problems. One of the problems that arise are student learning outcomes at the course of evolution tend to be low, because the students are not familiar with the assessment instruments developed higher-order thinking skills. Problem thinking skills of students that is low, overcome by applying authentic asessment in the textbook used. Qualitative test goal is to produce an authentic assessment of molecular evolution in the textbook is good, and can improve higher-order thinking skills of students. Qualitative test is one of the stages of research development, adapted from the model of the development of 4D-models Thiagarajan, ie develop stages. Qualitative test conducted on students of the Department of Biology State University of Malang, because the student has more accustomed to using assessment that guide higher-order thinking skills, so the results will be better. Qualitative assessment test showed that there were several assessment instruments that need to be revised, in accordance with the values obtained by the students on the posttest. Based on these results, it can be said that the authentic assessment in the textbook of molecular evolution has reached the category of good and fit for use in the teaching of Evolution in Higher Education.Kata kunci: uji kualitatif, asesmen autentik, buku ajar evolusi molekuler